Etika Investor dan Skandal Pasar Modal di Indonesia - Nazri, Ariadi; Albart, Nicko (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The aim of this research is to determine the influence of investor ethics on scandals that occur on the capital market in Indonesia (BEI). Investment Ethics has experienced very fast and high growth over recent time. The growth and development of this investment occurs both at the local level (Indonesia) and at the global level. In Indonesia, the growth and development of ethical investment can be seen from the increasing number of ethically based stock indices and the value of stock market capitalization in each of these indices. Meanwhile, at the global level, it can be seen from the increase in the value of ethical investment, especially in the five main world markets. The underlying basis for this phenomenon needs to be further explored regarding ethical investment issues. This article tries to explore ethical investment more deeply, especially regarding concepts, basis for decisions and approaches (strategies) in ethical investment activities. The reality of practice in the field shows that capital market activities (stock exchanges) are very vulnerable to various forms of crime which have very broad consequences for the economy and national stability. This can be seen from the increasing development of the capital market which is also accompanied by advances in technology and information in this era of globalization, it turns out that not only do you get convenience but there are also other consequences, both direct and indirect, that can threaten economic stability, especially in creating a market system. reasonable and orderly capital.